Case Report: A case of reversible tracheal diameter Mounier-Kuhn syndrome and literature review - Kong, Lu-xia; Li, Zhen-hua; Ni, Ji-xiang (Frontiers in Medicine, 2025)
Mounier-Kuhn syndrome (MKS), also known as tracheobronchomegaly (TBM) or tracheomegaly, is an extremely rare and chronic airway disease characterized by significant dilation of the trachea and central bronchi. Currently, there is a paucity of epidemiological studies on MKS, with the majority of data derived from case reports, resulting in limited understanding of this disease among clinicians. We encountered an 81-year-old male MKS patient whose diagnosis was delayed, and subsequently experienced a significant decrease in tracheal diameter post-diagnosis, marking the first documented case of reversible tracheal diameter in MKS patients. Concurrently, we conducted a review of 76 cases published within the past decade to procure comprehensive insights into the clinical characteristics of MKS patients. Based on our findings, we draw two key conclusions. First, at present, clinicians and radiologists have insufficient understanding of this disease, which often leads to missed diagnosis, misdiagnosis or delayed diagnosis. Second, the tracheal diameter of MKS has the potential to be reversible with appropriate treatment. This is the first case where the tracheal diameter has been found to be reversible.